Anticancer SAR establishment and novel accruing signal transduction model of drug action using biscoumarin scaffold. (December 2019) - Mayank,; Singh, Ashutosh; Kaur, Navneet; Garg, Neha; Singh, Narinder
Graphical abstract: Synthesized biscoumarin derivatives as anticancer lead were explored, showing promising anticancer potential by apoptosis induction. Kinesin spindle protein as its target receptor was finally established. Highlights: Anticancer activity of Biscoumarin scaffold was established. SAR and Apoptosis as a mechanism was explored. Kinesin Spindle Protein as a target was provided. Abstract: In this paper, we have established methylenebis (4-hydroxy-2H-chromen-2-one) as a promising anticancer scaffold with kinesin spindle protein (KSP) inhibitory activity under malignant condition. A series of biscoumarin derivatives (MN1 to MN30) with different substituent were synthesized, and their anticancer activity was explored. Six biscoumarin derivatives that were found active were further selected to formulate organic nanoparticles (ONPs). Anticancer activity of both the forms ( viz conventional and ONPs) was compared. MN30 was found most potent whereby MN10 showed good anticancer activity in both, i.e., conventional and ONP form; the structural activity relationship (SAR) study has been established. Computational investigation revealed biscoumarin scaffold as a suitable pharmacophore to bind against KSP protein. Molecular dynamics simulation studies revealed protein-ligand stability and dynamic behavior of biscoumarin-KSP complex. Finally, accruing signal transduction model was formulated to explain the observed MTT trend of conventional and ONP form. The model seems useful towards solving population specific varied results of chemotherapeutic agents. According to the model, MN10 and MN30 derivatives have good pharmacodynamics inertia and therefore, both the molecules were able to provide dose-dependent cytotoxic results.